AGROCHEMICAL ANALYSIS OF JAZZAKH REGION WITH POWERLY SALTY GRASS-GRAIN SOILS" (Spectrum Journal of Innovation, Reforms and Development, 2022)
When conducting research on the application of fertilizers on farm lands, crop rotation, tillage, irrigation regime of plants, agrochemical analysis of soil and plants reveals the qualitative and quantitative changes that occur in them. Shukhrat f / x, Davron f / x, Urin Bobo f / x, Shaxboz f / x, Usmon f / x, Shifobakhsh f / x, Otabek farms operating in the territory of Jizzakh district analysis results were obtained.In the agrochemical analysis of soils obtained from the above farms, the amount of mobile compounds of humus, phosphorus and potassium was determined.In conclusion, the results of the analysis show that the amount of nutrients in the lands of the above-mentioned farms is "very low" and "low". In addition, the supply of humus is "very low" and "low".